A PACKET CLASSIFICATION ALGORITHM ON MULTI-WAY PRIORITY TRIE - Nhat, Vu Duy; Nguyen Manh, Hung (Journal of Computer Science and Cybernetics, 2017)
Packet classification is a vital function of network devices such as routers, firewalls, IPS, IDS, etc. Speed of packet classification is a key factor that decides to bandwidth of a network equipment. The field of packet classification speed enhancement has attracted a significant number of researchers. In this paper, we propose a packet classification algorithm based on the idea of priority trie and multi-way trie. The accuracy and efficiency of the proposed algorithm are both theoretically and experimentally proved.